SISWA YANG KECANDUAN GAME ONLINE DAN KONDISI PSIKOLOGIS DI SMA TRI BHAKTI PEKANBARU - Setiawati, Linda; Yakub, Elni; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The phenomenon shows the much of students who play online games. Excessive students playing online games will make themselves addicted. Students who play these games online tend to have an emotional nature that affects themselves and others. One of the effects of online game addiction is declining learning achievement and anti social. The purpose of this research is 1) to know the description of online game addiction among students, 2) to know the description of the psychological condition of students who play online games. The population of this study is the students of class IX which consisting of 3 classes and the sample of this research as many as 28 students. The technique used is purposive sampling. This research is quantitative descriptive. Instrument data collection using a questionnaire which is then analyzed by classifying the data and technique the percentage. The results of this study is the duration of playing time 3-4 hours in a day; where online game play at home; types of games favored by students namely Mobile Legend and Dota; students who are addicted to online games have health problems on the eyes and hands and make the motivation to learn to decline; social adjustment of students who make relationships become tenuous and ignore others. While the psychological condition of students who are addicted to online games about their feelings is happy to return home early; the angry emotion experienced by the respondent is generally irritable when a friend says rudely; sad emotions experienced by respondents generally are disappointed when the desire is not met, then the fear of emotion experienced by respondents who are anxious when going to the exam because of lack of learning.Keywords: Addiction of online game, Psychological condition